Modular Irregular Labeling On Complete Graphs - Indah Chairun Nisa; Nurdin Nurdin; Hasmawati Basir (Universitas Negeri Makassar, 2022)
Let G be a simple graph of n order. An edge labeling such that the weights of all vertex are different and elements of the set modulo n, are called a modular irregular labeling. The modular irregularity strength of G is a minimum positive integer k such that G have a modular irregular labeling. If the modular irregularity strength is none, then we called the modular irregularity strength of G is infinity. In this article, we determine the modular irregularity strength of complete graphs.